Ecological contexts associated with early childhood curiosity: Neighborhood safety, home and parenting quality, and socioeconomic status - Shah, Prachi E.; Hirsh-Pasek, Kathy; Spinelli, Maria; Ozor, Jenny; Weeks, Heidi M.; McCaffery, Harlan; Kaciroti, Niko (Frontiers in Psychology, 2023)
Curiosity is an important social-emotional process underlying early learning. Our previous work found a positive association between higher curiosity and higher academic achievement at kindergarten, with a greater magnitude of benefit for children with socioeconomic disadvantage. Because characteristics of the early caregiving and physical environment impact the processes that underlie early learning, we sought to examine early environmental experiences associated with early childhood curiosity, in hopes of identifying modifiable contexts that may promote its expression. Using data from a nationally representative sample of 4750 children from the United States, this study examined the association of multi-level ecological contexts (i.e., neighborhood safety, parenting quality, home environment, and center-based preschool enrollment) on early childhood curiosity at kindergarten, and tested for moderation by socioeconomic status. In adjusted, stratified models, children from lower-resourced environments (characterized by the lowest -SES tertile) manifested higher curiosity if they experienced more positive parenting, higher quality home environments, and if they lived in “very safe” neighborhoods. We discuss the ecological contexts (i.e., parenting, home, and neighborhood environments) that are promotive of early childhood curiosity, with an emphasis on the role of the neighborhood safety and the “neighborhood built environment” as important modifiable contexts to foster early childhood curiosity in lower-resourced families.